The effect of perceived stress on organizational silence in emergency service doctors in Turkey: The mediating role of emotional intelligence - Erdoğan, Taskin; Bayraktar, Yusuf; Uçan, Fatih; Atilgan, Sait Sinan (Frontiers in Public Health, 2022)
Objectives: The purpose of this study is to determine the role of emotional intelligence in the relationship between the stress perceptions of emergency medicine doctors and their organizational silence behaviors. Methods: Data were collected digitally from 434 doctors working in emergency departments in Turkey. On the assumption that perceived stress was effective on organizational silence behavior and that emotional intelligence mediates this relationship, hypotheses were developed and a mediating effect model was established. The research model and hypotheses were shaped through Structural Equation Modeling (SEM). Hayes 4th model was used to test the research hypotheses. The research model was tested via SPSS Process v4.1 by Andrew F. Hayes. Results: According to the correlation analysis to determine the relationship between the variables, it was determined that perceived stress was positively correlated with organizational silence behavior, emotional intelligence was negatively correlated with perceived stress, and emotional intelligence was negatively correlated with organizational silence. As a result of the mediating effect model test, it was determined that emotional intelligence had a statistically significant mediating effect in the effect of perceived stress on organizational silence. Conclusion: Within the framework of the findings, it is thought that emotional intelligence is a key variable in turning the negative energy between stress and silence into positive.